2022
DOI: 10.1177/08862605221078812
|View full text |Cite
|
Sign up to set email alerts
|

Mock Jurors’ Perceptions of Child Sexual Abuse Cases: Investigating the Role of Delayed Disclosure and Relationship to the Perpetrator

Abstract: Child sexual abuse (CSA) claims brought forward weeks, months, or years after the alleged events are commonplace, yet the trial-level ramifications of delayed disclosure remain unclear. In the present study, we investigated the influence of length of delayed disclosure (1 day, 1 month, 10 months) as a function of the victim-perpetrator relationship (next-door neighbor, stepfather) on mock jurors’ perceptions of a CSA case. Jury-eligible participants (N = 328) read a mock trial summary describing an alleged inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Indeed, jurors rate children as more credible and render more guilty verdicts when the alleged perpetrator is nonfamilial (babysitter, stranger) rather than familial (uncle, father; Bornstein et al, 2007; Davies & Rogers, 2009). However, studies on this topic have not always yielded consistent effects on credibility and verdicts (Golding et al, 2020; Miller et al, 2022). Attorneys may not endorse the same misconceptions that jurors do by nature of their experiences in child sexual abuse cases.…”
Section: Plea Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, jurors rate children as more credible and render more guilty verdicts when the alleged perpetrator is nonfamilial (babysitter, stranger) rather than familial (uncle, father; Bornstein et al, 2007; Davies & Rogers, 2009). However, studies on this topic have not always yielded consistent effects on credibility and verdicts (Golding et al, 2020; Miller et al, 2022). Attorneys may not endorse the same misconceptions that jurors do by nature of their experiences in child sexual abuse cases.…”
Section: Plea Decisionsmentioning
confidence: 99%
“…Delays can lead to the loss of details or the decay of memory and result in inaccurate reporting (Gonzalves et al, 2022). Jurors seem to be attuned to this loss in accuracy, rating witnesses as less credible and rendering fewer guilty verdicts after longer compared with shorter delays of reporting (Miller et al, 2022; Pozzulo et al, 2010). Accordingly, prosecutors may be reluctant to move forward on a case that involves a longer delay between the alleged abuse and the disclosure, whereas defense attorneys may be more willing to fight these cases because they provide a clear avenue to impeach the credibility of the allegation.…”
Section: Plea Decisionsmentioning
confidence: 99%
“…For example, O'Connor et al (2023) found that ‘younger and older adults were implicitly biased to associate honesty more strongly with White children over Black children… Yet, when asked explicitly, Black children were rated as more honest than White children’ (p. 10; see also Goff et al, 2014). This adds to the fact that younger victims of sexual abuse (e.g., 5–10 years old) can be considered more credible than older victims (e.g., 15 years old) (Rogers et al, 2007; Voogt et al, 2020) and that children who take longer to disclose an abuse can be considered less credible (Miller et al, 2022). This is not to be overlooked because ‘credibility is an issue that pervades most trials, and at its broadest may amount to a decision on guilt or innocence’ (R. v. Handy, 2002, p. 951).…”
Section: The Impact Of Demeanour For Child Witnessesmentioning
confidence: 99%